Clinicopathological and immunohistochemical features of pleomorphic lobular mammary carcinoma in a female dog - Magalhães, Geórgia M.; Santilli, Juliana; Cintra, Priscila P.; Calazans, Sabryna G.; Ribeiro-Silva, Alfredo (Brazilian Journal of Veterinary Pathology, 2020)
This report describes a pleomorphic lobular carcinoma (PLC) case, in an eight-year-old, female Shih Tzu dog, which attended the Veterinary Hospital of the University of Franca, Brazil. A single irregular, non-ulcerated, non-hyperaemic soft nodule, 2 cm in diameter, was observed during the clinical examination. The nodule was adhered within the deep tissues in the right caudal thoracic mammary gland. After removal of the nodule, the histopathologic examination showed that the neoplastic epithelial cells were scattered throughout the stroma in linear patterns, had abundant eosinophilic cytoplasm, eccentric nuclei and cytoplasmatic vacuoles, features compatible with the diagnosis of pleomorphic lobular carcinoma. An immunohistochemical evaluation was performed in order to better characterise the tumour. Based on the negative immunoreactivity for hormone receptors and human epidermal growth factor receptor-2 and positive expression for one of the basal markers, the basal-like triple-negative phenotype was characterized. The treatment indicated was chemotherapy with carboplatin; however, the disease progressed, and the patient had an overall survival of 47 days after surgery, confirming the aggressiveness of the disease.